IDENTIFIKASI PERUBAHAN TUTUPAN DAN PENGGUNAAN LAHAN SEBAGAI DASAR PENENTUAN STRATEGI PENGELOLAAN KPHP WAY TERUSAN - Tri Santoso; Melya Riniarti; Indra Gumay Febryano (Universitas Lambung Mangkurat, 2017)
Encroachment on forest areas in Indonesia occurs due to various factors mainly related to tenure issues and economic interests. That encroachment occurred in all regions of Indonesia with vary in intensity and amount. Register 47 Way Terusan which has been designated as a KPHP model Way Terusan also being occupied by squatters since the 1990s. The communities within and around the KPHP Way Terusan area has highly dependency on forest resources. The data collection is done in several ways, namely: interviews, literature searches, downloads Landsat satellite imagery and field verification activities. Landsat images Scene: Path 123 and Row 063 for the year 1994, 1999, 2004, 2009 and 2014. Data analysis was conducted using NDVI (Normalized Difference Vegetation Index) and supervised classification. The results of the analysis of land cover in 1994 until 2014 shows the intensity of dynamics of land cover change in the region KPHP Way Terusan. Land cover changes caused as a result of choice of the type of vegetation that has higher economic value. In 2014, the use of cassava cultivation was the highest (55.24%) because of its high economic value, convenient cultivation and market demand. Partnership with agroforestry pattern most likely applied as management strategy policies to accommodate the interests of various stakeholders in KPHP Way Terusan.